TRAINING OF TEACHERS WORKING IN THE EDUCATION OF YOUTH AND ADULTS IN SPACES OF DEPRIVATION OF LIBERTY - Maciel Jose, Gesilane de Oliveira; Ferrari Leite, Yoshie Ussami [UNESP] (Fundacao Univ Tocantins, 2021)
The present work seeks to reflect on the training of teachers who teach in the education of young people and adults in schools inserted in prisons. Educational assistance requires a process of teacher reconfiguration to assist people deprived of their liberty, considering that the proposal for education in prison aims at the recovery and social reintegration of the individual. From the analysis of narrative interviews, it is evident that the formative process is considered insufficient and fragile in face of the challenges that educators experience in their daily lives. Therefore, training that meets the specificities of the prison context is necessary, guided by the principles of popular education, human rights, the intellectual autonomy of the teacher and a conception supported by the technical, aesthetic, political and ethical dimensions of teaching.
Keywords: Teacher training; Education in prisons; People deprived of liberty; Narrative interview